Case Study: Voxy "English for Software Engineering" – The Conception and Creation of an E-Learning English-Language Course Tailored to Learners’ Real-World Needs - Nielson, Katharine B (International Journal of Advanced Corporate Learning (iJAC), 2018)
This case study provides an overview of Voxy’s language-learning platform and the needs analysis conducted to determine the content required for its “English for Software Engineering” course, which received a 2018 International E-Learning Award in the Business Division. This study documents Voxy’s methodology and theoretical underpinnings. Further, the report outlines the rationale behind using authentic, real-world content, how the company identified the English skills that software engineers require to do their jobs, and how a team of working software engineers provided both guidelines and raw materials to help develop the course content.